A Systematic Review of Serum Biomarkers Anti-Cyclic Citrullinated Peptide and Rheumatoid Factor as Tests for Rheumatoid Arthritis. (11th September 2011) - Taylor, Peter; Gartemann, Juliane; Hsieh, Jeanie; Creeden, James
Abstract : This systematic review assesses the current status of anti-cyclic citrullinated peptide (anti-CCP) and rheumatoid factor (RF) tests in the diagnosis and prognosis of rheumatoid arthritis (RA). We reviewed publications on tests and biomarkers for early diagnosis of RA from English-language MEDLINE-indexed journals and non-MEDLINE-indexed sources. 85 publications were identified and reviewed, including 68 studies from MEDLINE and 17 non-MEDLINE sources. Anti-CCP2 assays provide improved sensitivity over anti-CCP assays and RF, but anti-CCP2 and RF assays in combination demonstrate a positive predictive value (PPV) nearing 100%, greater than the PPV of either of the tests alone. The combination also appears to be able to distinguish between patients whose disease course is expected to be more severe and both tests are incorporated in the 2010 ACR Rheumatoid Arthritis Classification Criteria. While the clinical value of anti-CCP tests has been established, differences in cut-off values, sensitivities and specificities exist between first-, second- and third-generation tests and harmonization efforts are under way. Anti-CCP and RF are clinically valuable biomarkers for the diagnosis and prognosis of RA patients. The combination of the two biomarkers in conjunction with other clinical measures is an important tool for the diagnosis and management of RA patients.